World Malaria Report 2013 - WHO (World Health Organization, 2014)
This edition of the World Malaria Report summarizes thecurrent status of malaria control worldwide. It reviews progresstowards internationally agreed goals and targets anddescribes trends in funding intervention coverage andmalaria cases and deaths. In 2013 there are 97 countries and territories with ongoingmalaria transmission and 6 countries in the prevention of reintroductionphase making a total of 103 countries and territoriesin which malaria is presently considered endemic. Globally an estimated 3.4 billion people are at risk of malaria. WHO estimatesthat 207 million cases of malaria occurred globally in 2012(uncertainty range 135?287 million) and 627 000 deaths (uncertaintyrange 473 000?789 000). Most cases (80%) and deaths (90%) occurred in Africa andmost deaths (77%) were in children under 5 years of age. The World Malaria Report presents a critical analysis and interpretationof data provided by national malaria control programmes(NMCPs) in endemic countries. Standard reporting forms weresent in April 2013 to the 97 countries with ongoing malariatransmission and to 5 of the countries that recently entered theprevention of reintroduction phase. Information was requestedon (i) populations at risk; (ii) vector species; (iii) number of cases admissions and deaths for each parasite species; (iv) completenessof outpatient reporting; (v) policy implementation; (vi)commodities distributed and interventions undertaken; (vii)results of household surveys; and (viii) malaria financing.Table 1.2 summarizes the percentage of countries respondingby month and by WHO region in 2012.Information from household surveys was used to complementdata submitted by NMCPs notably the demographic and healthsurveys (DHS) multiple indicator cluster surveys (MICS) andmalaria indicator surveys (MIS). These surveys provide informationon the percentage of the population that sleeps under amosquito net and the percentage of children with fever who aretreated and the medication they receive. Information on malariafinancing was obtained from the Organisation for EconomicCo-operation and Development (OECD) database on foreignaid flows and directly from the Global Fund to Fight AIDS Tuberculosis and Malaria (Global Fund) and the US President?sMalaria Initiative (PMI).Data were analysed by WHO staff at headquarters and regionaloffices with extensive consultation with WHO country officesand NMCPs regarding the interpretation of country information.Assistance in data analysis and interpretation was also providedby the African Leaders Malaria Alliance (ALMA) the Child HealthEpidemiology Reference Group (CHERG) the Institute of HealthMetrics and Evaluation (IHME) the Malaria Atlas Projectthe US Centers for Disease Control and Prevention (CDC) andthe Global Fund. The following chapters consider the policies and interventionsrecommended by WHO the implementation of interventions and the impact of these interventions on malaria cases anddeaths from a global and a regional perspective.Chapter 2 summarizes the WHO policy-setting process and thepolicies and strategies recommended by WHO to achieve theinternationally agreed goals for malaria control and elimination.It describes the goals and targets for malaria control and elimination and recommended indicators of progress.Chapter 3 reviews recent trends in international and domesticfinancing in relation to the resource requirements for meetingglobal malaria control targets. It examines the distribution ofmalaria funding by WHO region by gross national income (GNI)per capita and by malaria mortality rate of a country. It alsoreviews endemic countries? willingness to pay for malaria control.Chapter 4 reviews the commodity needs for malaria vectorcontrol. It considers the policies that national programmes haveadopted for vector control implementation and the progressmade towards universal access to ITNs and IRS. An update isprovided on the growing problem of insecticide resistance andthe appropriate monitoring and management of resistance.Chapter 5 reviews progress in implementation of chemoprevention particularly the intermittent preventive treatment ofmalaria in pregnancy and in infants and the introduction ofseasonal chemoprevention in older children. It also reports onthe current status of malaria vaccine development.Chapter 6 reviews the commodity needs for malaria diagnostictesting and treatment. It reports on the extent to which nationalprogrammes have adopted policies for universal diagnostictesting of suspected malaria cases and examines trends in theavailability of parasitological testing. It also reviews the adoptionof policies and implementation of programmes for improvingaccess to effective treatment for malaria. Finally this chapterreports on progress in the withdrawal of oral artemisinin-basedmonotherapies from the market the current status of drug efficacymonitoring recent trends in antimalarial drug resistanceand efforts to contain artemisinin resistance.Chapter 7 examines the extent to which data are available formonitoring progress towards international targets and how thishas changed since 2000.Chapter 8 reviews trends in reported malaria cases for 62 countriesthat have reported consistently between 2000 and 2012. For countries with low numbers of cases it summarizes theirprogress towards elimination. This chapter also presents an analysisof the estimated numbers of cases and deaths for countrieswith ongoing transmission between 2000 and 2012.Regional profiles are provided. These summarize the epidemiologyof malaria in each WHO region trends in malaria caseincidence and the links between malaria trends and malariaprogramme implementation. Country profiles are also provided for countries with ongoingmalaria transmission and those recently progressing to theprevention of reintroduction phase. These profiles are followedby Annexes which give data by country for the malaria-relatedindicators.